2018
DOI: 10.3390/ijerph15112471
|View full text |Cite
|
Sign up to set email alerts
|

Internet Risks: An Overview of Victimization in Cyberbullying, Cyber Dating Abuse, Sexting, Online Grooming and Problematic Internet Use

Abstract: The advance of digital media has created risks that affect the bio-psycho-social well-being of adolescents. Some of these risks are cyberbullying, cyber dating abuse, sexting, online grooming and problematic Internet use. These risks have been studied individually or through associations of some of them but they have not been explored conjointly. The main objective is to determine the comorbidity between the described Internet risks and to identify the profiles of victimized adolescents. An analytical and cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
120
2
42

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(175 citation statements)
references
References 61 publications
(127 reference statements)
11
120
2
42
Order By: Relevance
“…Not recognizing some abuse behaviors increases the probably of suffering victimization because victims are not fully aware of abusive behaviors [52]. Adolescents' beliefs in romantic myths could make them believe that certain abusive, controlling and jealous behaviors are signs of love and are normal behaviors in a romantic relationship [39,41,42,47,53]. In line with this, some previous studies have linked offline DV victimization with myths of romantic love [47,48,50,51,54,55].…”
Section: Myths Of Romantic Love and Cyber Dating Violence Victimizationmentioning
confidence: 91%
See 1 more Smart Citation
“…Not recognizing some abuse behaviors increases the probably of suffering victimization because victims are not fully aware of abusive behaviors [52]. Adolescents' beliefs in romantic myths could make them believe that certain abusive, controlling and jealous behaviors are signs of love and are normal behaviors in a romantic relationship [39,41,42,47,53]. In line with this, some previous studies have linked offline DV victimization with myths of romantic love [47,48,50,51,54,55].…”
Section: Myths Of Romantic Love and Cyber Dating Violence Victimizationmentioning
confidence: 91%
“…Offline DV victimization in a romantic relationship negatively affects adolescents' well-being and has been related to stress, anxiety, less satisfaction with life, poor academic achievement, low self-esteem, substance abuse, and eating disorders [30,31,33,36,37]. Positive correlations among different forms of offline DV victimization (physical, verbal-emotional, and relational) have been observed [38], and it has also been suggested that being victimized in one social context increases the probability of being victimized in other social contexts, which could increase the possibility of suffering poly-victimization [39][40][41][42][43][44]. However, no study has yet explored if different forms of offline DV victimization, such as physical, verbal-emotional or relational victimization, have varying predictive weights in relation to distinct forms of cyber DV victimization: cyber-control and cyber-aggression.…”
Section: Offline and Cyber Dating Violence Victimizationmentioning
confidence: 99%
“…Previous studies found that peer bullying was significantly associated with IGD among college students [29] and pathological Internet use among adolescents [30]. Online bullying has also been anecdotally and empirically linked to multiple maladaptive emotional and behavioral outcomes among adolescents, such as depression, substance use, and suicide [31,32]. Yet, our literature search did not locate any studies that examined the association between online/peer bullying and adolescent IGD.…”
Section: Introductionmentioning
confidence: 97%
“…As a result, we are now getting used to concepts such as cyberstalking, doxing, phishing, grooming, or sextortion. These new offences have been widely described in the literature [11,12].…”
Section: Featured Application: a Complete Review Of Information And Cmentioning
confidence: 99%
“…As a result, we are now getting used to concepts such as cyberstalking, doxing, phishing, grooming, or sextortion. These new offences have been widely described in the literature [11,12].In addition to these expressions of violence, the cyber environment also reproduces the general gender gap that exists in society [13]. Combined with gender pay gap and the other inequalities present in our world, the terms "digital gender gap" or "digital gender divide", involve a social issue referring to the differing amount of information between those who have access to the internet (especially broadband access) and those who do not, as described in terms of gender.…”
mentioning
confidence: 89%